Genetics of Recurrent Vertigo and Vestibular Disorders - Gazquez, Irene; A. Lopez-Escamez, Jose (Current Genomics, 2011)
We present recent advances in the genetics of recurrent vertigo, including familial episodic ataxias, migraneous vertigo, bilateral vestibular hypofunction and Meniere's disease. Although several vestibular disorders are more common within families, the genetics of vestibulopathies is largely not known. Genetic loci and clinical features of familial episodic ataxias have been defined in linkage disequilibrium studies with mutations in neuronal genes KCNA1 and CACNA1A. Migrainous vertigo is a clinical disorder with a high comorbidity within families much more common in females with overlapping features with episodic ataxia and migraine. Bilateral vestibular hypofunction is a heterogeneous clinical group defined by episodes of vertigo leading to progressive loss of vestibular function which also can include migraine. Meniere's disease is a clinical syndrome characterized by spontaneous episodes of recurrent vertigo, sensorineural hearing loss, tinnitus and aural fullness and familial Meniere's disease in around 10-20%of cases. An international collaborative effort to define the clinical phenotype and recruiting patients with migrainous vertigo and Meniere's disease is ongoing for genome-wide association studies.
Keywords: recurrent vertigo